JUVENALIAN SATIRE AND MORAL OUTRAGE IN ENGLISH LITERATURE: FROM SWIFT TO ORWELL - Abdullaeva Iroda Murotovna (Modern American Journals, 2026)
The article is devoted to an analysis of the Juvenalian tradition of satire in English literature of the eighteenth to twentieth centuries, based on the works of Jonathan Swift and George Orwell. Juvenalian satire is examined as a form of literary expression grounded in moral indignation, invective, and the exposure of social vices. The article traces the evolution of this tradition from the Enlightenment context of the early eighteenth century to the politically engaged prose of the twentieth century. Special attention is given to artistic strategies, the rhetoric of indignation, and the ethical stance of the satirist, as well as to the transformation of the addressee of satirical discourse.
Keywords: Juvenalian satire, moral indignation, English literature, Swift, Orwell, social criticism, invective.